Implementasi Algoritma Kriptografi Caesar Cipher dan Rail Fence Cipher untuk Keamanan Data Teks Menggunakan Python - Dewi Purnamasari (Universitas Ivet, 2021)
Security and confidentiality in communicating become a necessity so that the information sent and received is not misused by irresponsible parties. Cryptography not only provides a tool for information security but is also a useful technique for the security and confidentiality of information. This study aims to implement the Caesar Cipher and Rail Fence Cipher algorithms to determine the encoding process and also to determine the effectiveness of the encryption time and description of the two cryptographic techniques. The processing time of the two methods shows that the description time is longer than the encryption process. The average execution time of the Caesar Cipher algorithm is faster than the Rail Fence Cipher. The average encryption time is 0.0000802 second and the description time is 0.000131 second, however Rail Fence is more secure because the text process is sent in a zig zag form, so the received ciphertext is more secure than Caesar Cipher. Caesar Cipher is faster because the letter encoding process is shifted as many keys as desired. Keywords: Caesar Cipher, Rail Fence Cipher, Key, ziq zaq, Plaintext, Chipertext